Magnetically Guided Nanoworms for Precise Delivery to Enhance In Situ Production of Nitric Oxide to Combat Focal Bacterial Infection In Vivo - Lu, Bitao; Hu, Enling; Xie, Ruiqi; Yu, Kun; Lu, Fei; Bao, Rong; Wang, Chenhui; Lan, Guangqian; Dai, Fangyin (ACS applied materials & interfaces, 2021)
Overexploitation of antibiotics increases the emergence of multidrug-resistant agents (MDRAs), which may potentially cause a global crisis with severe health consequences. Hence, there is great demand for next-generation antibacterial platforms based on antibiotic-free strategies or targeted therapies to mitigate the emergence of MDRAs. Herein, an all-in-one hollow nanoworm (A-Fe/AuAg@PDA) is developed with a core comprising citrate-capped Au-Ag nanoparticles (Cit-AuAg NPs) loaded with Fe O and an l-arginine (L-Arg)-modified polydopamine (PDA) outer shell, possessing exceptional magnetic-targeting ability and a photothermal therapeutic effect. Following intravenous injection, A-Fe/AuAg@PDA can be precisely delivered to the targeted infection sites by an externally applied magnetic field. The in situ produced NO, together with Ag ions and reactive oxygen species, synergistically results in the highly effective elimination of in vivo bacterial infection. With the aid of functional worm-like A-Fe/AuAg@PDA nanocarriers possessing superior biocompatibility, the combination of magnetic guidance therapy and near-infrared-triggered in situ generation of NO may provide a novel approach for eradicating abscesses in the body. To our knowledge, this is the first study highlighting the magnetically guided delivery of worm-like nanocarriers for the antibiotic-free therapy of bacterial infections using in situ generated NO gas, which demonstrates high potential for application in clinical gas therapy.